2021
DOI: 10.3390/su13041989
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Businesses Development Affect Bioenergy Industry Growth under the Pathway of Sustainable Development?

Abstract: The Treaty of European Union (EU) sets out the EU vision for sustainable development of Europe based on balanced economic growth and price stability, a highly competitive social market economy, aiming at full employment and social progress, and a high level of protection and improvement of the quality of the environment. This led us to ask whether or not social business development stimulates the development of the bioenergy sector in the EU28 countries. Given the increasing rates of energy insecurity, environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
0
7
1
Order By: Relevance
“…In particular, the impact magnitudes are 0.039 and 0.070 for EU13 and 0.016 and 0.051 for EU15 members, respectively. This indicates that a remarkable transformation in the natural landscape can occur in EU13 underdeveloped countries by increasing carbon dioxide and population density than in EU15 developed countries [71,72]. On the other hand, the findings show that the positive influence of economic growth on land-use change is greater in the EU15 members than in the EU13 members.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, the impact magnitudes are 0.039 and 0.070 for EU13 and 0.016 and 0.051 for EU15 members, respectively. This indicates that a remarkable transformation in the natural landscape can occur in EU13 underdeveloped countries by increasing carbon dioxide and population density than in EU15 developed countries [71,72]. On the other hand, the findings show that the positive influence of economic growth on land-use change is greater in the EU15 members than in the EU13 members.…”
Section: Discussionmentioning
confidence: 82%
“…Fourth, bioenergy is also a solution to encourage local, regional, and national economies through agricultural development. The demand for bioenergy raw materials will encourage an increase in biomass production from domestic resources, which in turn will encourage the growth of the bioenergy industry, expansion of employment opportunities, increased state revenues, and economic growth [29].…”
Section: Resultsmentioning
confidence: 99%
“…The productivity of resources, especially bioenergy, has been shown to affect economic growth [2]. As a result, it is clear that the expansion of the bioenergy business aids the reduction in pollution and unemployment [3]. Several authors have concluded that bioenergy has a significant role to play in the decarbonization of society.…”
Section: Introductionmentioning
confidence: 99%